2021
DOI: 10.1101/2021.05.05.442849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methylation calling tools for Oxford Nanopore sequencing: a survey and human epigenome-wide evaluation

Abstract: Background: Nanopore long-read sequencing technology greatly expands the capacity of long-range single-molecule DNA-modification detection. A growing number of analytical tools have been actively developed to detect DNA methylation from Nanopore sequencing reads. Here, we examine the performance of different methylation calling tools to provide a systematic evaluation to guide practitioners for human epigenome-wide research. Results: We compare five analytic frameworks for detecting DNA modification from Nanop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Here we represent the first comprehensive comparison of computational tools focused on detecting m6A in the ONT DRS dataset. Rational oligo models and well-established BS-seq data have already been applied to the benchmarking of 5mC detection by nanopore sequencing 44,45 . However, there is no gold-standard method for m6A detection with both single-base resolution and stoichiometric information on the NGS platform.…”
Section: Discussionmentioning
confidence: 99%
“…Here we represent the first comprehensive comparison of computational tools focused on detecting m6A in the ONT DRS dataset. Rational oligo models and well-established BS-seq data have already been applied to the benchmarking of 5mC detection by nanopore sequencing 44,45 . However, there is no gold-standard method for m6A detection with both single-base resolution and stoichiometric information on the NGS platform.…”
Section: Discussionmentioning
confidence: 99%
“…Calling DNAm from Nanopore sequencing data is a computational challenge to classify methylated and unmethylated cytosines based on the electrical signal emitted as the DNA passes through the pore with a number of algorithms developed for this purpose. In this study we implemented just one of these algorithms, Nanopolish(4), which was found to be consistently one of the most accurate and concordant with the other best performing methods, across a range of genomic contexts, as well as the least computationally intensive (21). One limitation of this algorithm is that it only considers CpGs and ignores DNAm at cytosines in other genomic contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In real-time single molecule sequencing approaches, methylation impacts the kinetics of the polymerase while incorporating fluorescently labeled nucleotides into nucleic acid strands during DNA sequencing: base modifications alter both pulse width and interpulse duration, allowing the detection of epigenetics changes (Flusberg et al, 2010). In nanoporebased technologies, the electric current pattern is different for modified and non-modified bases and methylation state can be predicted with specific tools (Liu et al, 2021).…”
Section: Application Of Lrs To the Diagnosis Of Imprinting Disordersmentioning
confidence: 99%